Task-Oriented Communication Design at Scale - Mostaani, Arsham; Vu, Thang X.; Habibi, Hamed; Chatzinotas, Symeon; Ottersten, Bjorn (IEEE transactions on communications, 2025)
With countless promising applications in various domains such as IoT and Industry 4.0, task-oriented communication design (TOCD) is getting accelerated attention from the research community. This paper presents a novel approach for designing scalable task-oriented quantization and communications in cooperative multi-agent systems (MAS). The proposed approach utilizes the TOCD framework and the value of information (VoI) concept to enable efficient communication of quantized observations among agents while maximizing the average return performance of the MAS, a parameter that quantifies the MAS's task effectiveness. The computational complexity of learning the VoI, however, grows exponentially with the number of agents. Thus, we propose a three-step framework: (i) learning the VoI (using reinforcement learning (RL)) for a two-agent system, (ii) designing the quantization policy for an N-agent MAS using the learned VoI for a range of bit-budgets and, (iii) learning the agents' control policies using RL while following the designed quantization policies in the earlier step. Our analytical results show the applicability of the proposed framework under a wide range of problems. Numerical results show striking improvements in reducing the computational complexity of obtaining VoI needed for the TOCD in a MAS problem without compromising the average return performance of the MAS.